Inpatient burden of lung cancer and changes after a hospital performance reform: a real-world study - Han, Binbin; Chen, Xiaofang (Frontiers in Oncology, 2026)
BackgroundLung cancer places a substantial burden on hospital inpatient care, particularly in tertiary cancer centers. Evidence remains limited on how hospital performance-based management reforms are associated with inpatient efficiency and costs among patients with lung cancer.MethodsWe conducted a retrospective, real-world study using inpatient administrative data from a tertiary cancer hospital in China between 2016 and 2020. Hospitalizations (admissions) of patients with lung cancer were identified, and patient records were linked to enable secondary patient-level analyses. Length of stay (LOS) and daily hospitalization costs were evaluated as complementary indicators of inpatient efficiency and resource utilization intensity. A hospital performance reform implemented in April 2018 was examined by comparing pre-reform (2016–2017) and post-reform (2019–2020) periods. An interrupted time series analysis (ITSA) was conducted using segmented regression on monthly geometric means of log-transformed outcomes at the hospitalization level. Multivariable patient-level regression analyses were conducted as secondary analyses.ResultsA total of 25,331 patients hospitalized with lung cancer were included. After April 2018, LOS declined by approximately 1.6% per month (p < 0.001) relative to the pre-reform trend, while daily hospitalization costs increased by approximately 2.1% per month (p < 0.001) relative to the pre-reform trend. Patient-level analyses were directionally consistent, with the post-reform period associated with a 16.0% shorter LOS and a 31.9% higher daily cost. Sensitivity analyses excluding 2020 and restricting to index admissions yielded similar results.ConclusionsAmong patients hospitalized with lung cancer, the hospital performance reform implemented in 2018 was associated with shorter hospitalization duration and higher daily costs. These findings suggest concurrent changes in inpatient efficiency and resource utilization intensity and highlight the importance of using complementary indicators when evaluating hospital management reforms in oncology care.